Operational Risk Management: A Survey of Systems, Strategies and Preparedness of Indian Banks - Mehra, Yogieta S.; Agrawal, Rashmi (Indian Journal of Finance, 2011)
The study aims to explore the present status of management practices of operational risk, strategies followed, key determining factors and limitations being faced by a cross-section of Indian Banks in the management of operational risk. An analysis of Indian scenario was performed through execution of a survey comprising of a questionnaire. The questionnaire was addressed to Chief risk officers / Employees in the risk management / Operational risk management department of 31 banks. The Reliability Analysis using Cronbach Alpha model was used to test the reliability of the questionnaire. Thereafter, Factor Analysis was performed on different sections of the questionnaire to extract the most important variables which differentiate performance of one bank from others. KMO Measure of Sampling Adequacy and Bartlett's test of sphericity were used to justify the use of factor analysis as a data reduction technique. The study provides a conclusive evidence of heightened awareness and due importance given to operational risk by Indian banks. The sub-prime crisis has made the organizations more conscious and as a result, all new products are subject to risk review and sign-off process for identification and assessment of relevant risks. Size was observed to be a deterrent to collection of external loss data and formation of an operational risk framework. Level of involvement of operational risk functionaries was observed to be relatively deeper in large banks. Attrition rate was observed to be the highest amongst New Private (Sector) Banks. The performance/preparedness of average and small sized public sector and old private sector banks was observed to be lagging behind that of new private sector banks in effectiveness of operational risk framework, effectiveness of internal controls, responsiveness of business to operational risk department among others.